The Effect of Financial Constraints and Corporate Governance on Environmental Performance - Hanna, Nunggi Safriatul; Hudayati, Ataina (Journal of Social Work and Science Education, 2025)
This study investigates the impact of financial constraints and corporate governance on a company's environmental performance. The independent variables used in this study are financial constraints, managerial ownership, institutional ownership, and audit committees. The dependent variable in this study is environmental performance. Additionally, it controls for variables such as company size and profitability. This study uses a sample of 185 data points from mining sector companies listed on the Indonesia Stock Exchange (IDX) during the 2021-2023 period. By using a quantitative approach in the form of panel data regression as a data analysis method, it shows that financial constraints, managerial ownership, and audit committees have a positive effect on environmental performance. While institutional ownership hurts environmental performance. The integration of financial constraints and corporate governance as comprehensive determinants of environmental performance is still rarely explored together in the Indonesian context, especially in the mining sector, which has a significant environmental impact. This study is expected to contribute to the understanding of financial constraints, corporate governance, company size, and profitability regarding how these factors interact to influence environmental performance. In addition, this study is also expected to be a reference for further research on financial constraints, corporate governance, environmental performance, company size, and profitability. This research not only makes academic contributions but also has significant practical implications for companies, stakeholders, and policymakers in improving environmental performance.